Regulation of leukotriene B4 generation from human polymorphonuclear granulocytes after stimulation with formyl-methionyl-leucyl phenylalanine: effects of pertussis and cholera toxins. - Hensler, T (1991)
The effects of holotoxins and toxin subunits from Bordetella pertussis and Vibrio cholerae strains on intact and digitonin-permeabilized human polymorphonuclear neutrophils were studied. Our data clearly demonstrate that formyl-methionyl-leucyl-phenylalanine (fMLP)-induced generation of chemotactic active leukotriene B4 was inhibited by both holotoxins as well as by their isolated enzymatic A protomers. In contrast, the respective binding components (B oligomers) did not affect leukotriene formation. Priming of digitonin-permeabilized neutrophils with either guanylylimidodiphosphate or inositol trisphosphate increased subsequent stimulation with fMLP. In contrast, diacylglycerol decreased fMLP-induced leukotriene B4 formation, but inositol trisphosphate and diacylglycerol had no effect on inhibition mediated by the toxins. In addition, pertussis and cholera toxins reduced the specific binding of [3H]fMLP. Scatchard plot analysis revealed that the observed decrease of peptide binding was due to a reduced number of receptor sites. The fMLP-stimulated [3H]guanylylimidodiphosphate binding and GTPase activity used as parameters for the activation of G proteins were decreased in parallel. These results suggest altered chemotactic receptor numbers and G-protein functions responsible for the toxin-dependent suppression of fMLP-mediated response for neutrophils.